GEL CASTING METHOD FOR COMPLEX-SHAPED DENSE CERAMIC FABRICATION - Ike Setyorini; Ria Julyana Manullang; Karlina Noordiningsih; Hernawan Hernawan (Jurnal Keramik dan Gelas Indonesia, 2019)
The fabrication of complex-shaped dense ceramic has been done by gel casting method. Alumina was used as raw material in this study. Alumina was mixed with methacrylamide (MAM) dispersant and Methylenebisacrylamide (MBAM) monomer with a certain ratio until the suspension has a good ability to flow. Ammonium persulphate (APS) as an initiator and Tetra-methylethylene diamine (TEMED) as catalyst were added to accelerate the polymerization reaction. The suspension was then poured into wax mold, stayed until harden and burned at 1300 oC. The results showed the minimum viscosity of suspension is obtained with 80% alumina content and addition of dispersant at 0.15% weight of alumina. The addition of APS and TEMED at 0.2% weight of monomer solution and the addition of PEG at 1 µl per gram alumina provided the best mechanical strength of green body at 61.29 kg/cm2 . Addition of PEG was used to overcome the problem of lamination due to oxidation reactions by air